Case Report: A Rare Case of Right-Sided Papillary Fibroelastoma in a 1-Year-Old With Congenital Heart Disease - Ahmad, Ali; El-Am, Edward A.; Kurmann, Reto D.; Hagler, Donald J.; Bois, Melanie C.; Maleszewski, Joseph J.; Klarich, Kyle W. (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Cardiac papillary fibroelastomas (PFEs) are the most common primary benign cardiac tumors, although they are somewhat unusual in children and typically seen on the left-sided cardiac valves. Case summary: A 10-week-old patient was found to have a partial atrioventricular canal defect, with associated tricuspid and mitral regurgitation. He was medically managed until 1 year of age, when surgical correction was done. During the procedure, a PFE was found incidentally on the TV. Conclusion: This is one of the youngest patients to be reported with PFE, thus adding to the literature of these unusual cases in children.